Intikhab-e-Kalam : Parveen Shakir - Parveen Shakir; Edited and introduced by Fatima Hassan (Karachi Oxford University Press, 2016)
This is a representative selection of the poetry of Parveen Shakir, who came into the literary limelight after the publication of her first poetry collection Khushboo (1976), which won the Adamjee Literary Award. Along with Khushboo, her three further collections Sadbarg, Khudkalami and Inkaar were published together under the title Mah e Tamam during her lifetime A further poetry collection Kaf e Aaina and selection of newspaper columns Gosha e Chashm were published posthumously. Since her untimely death, she is regarded as having been a very important modern Urdu language poet. She was awarded the ''Pride of Performance'', one of Pakistan's highest civilian awards for his outstanding contributions to Urdu literature.
Keywords: Urdu Literature - Poetry -- Poetry in Urdu -- Urdu Literature - Poetry -- Intikhab e Kalam : Parveen Shakir